2009
DOI: 10.1136/ard.2009.107649
|View full text |Cite
|
Sign up to set email alerts
|

Systemic levels of IL-23 are strongly associated with disease activity in rheumatoid arthritis but not spondyloarthritis

Abstract: Th17-related cytokines are expressed in joints of spondyloarthritis as well as RA patients. IL-23 levels, however, correlate with disease activity parameters in RA only. These results point towards a differential regulation of the Th17 cytokine system in spondyloarthritis compared with RA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
77
5
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(99 citation statements)
references
References 45 publications
16
77
5
1
Order By: Relevance
“…Given that IL-23 shares the same protein subunit of IL-12p40, it can be concluded that IL-23 is the key pathological cytokine in joint inflammation. To support this theory is the discovery of significantly higher levels of IL-23 in both serum and synovial fluid of RA patients (Melis et al, 2010). Results from our unpublished studies with recombinant IL-23 in CIA mice have yielded interesting findings.…”
Section: Il-12 and Il-23 Are The Critical Cytokines Involved In Jointsupporting
confidence: 49%
See 1 more Smart Citation
“…Given that IL-23 shares the same protein subunit of IL-12p40, it can be concluded that IL-23 is the key pathological cytokine in joint inflammation. To support this theory is the discovery of significantly higher levels of IL-23 in both serum and synovial fluid of RA patients (Melis et al, 2010). Results from our unpublished studies with recombinant IL-23 in CIA mice have yielded interesting findings.…”
Section: Il-12 and Il-23 Are The Critical Cytokines Involved In Jointsupporting
confidence: 49%
“…Th17 development is governed by TGF, IL-1 and IL-23 (Paradowska-Gorycka et al, 2010;Santarlasci et al, 2009). Higher concentrations of IL-23 (a member of the IL-12 family cytokines) are detected in the serum and synovial fluid of patients with greater severity of RA (Melis et al, 2010). IL-23 can also be produced by osteoblast cells after stimulation with TNF (unpublished data).…”
Section: Introductionmentioning
confidence: 99%
“…29 The concentrations of the cytokines measured in our study are consistent with those reported in other studies. 30,31 Although IL1b has been shown to correlate with RA disease severity, 32 our data suggest it is largely independent of the other cytokines measured, and tends to be present in large amounts or not at all. This most likely reflects a different inflammatory pathway dominating in these patients.…”
Section: à5mentioning
confidence: 81%
“…Similar to ␥␦ T cells, Th17 cells express IL-23R, which induces IL-17A production and cell proliferation (2,24). In addition to its protective roles, IL-23 potentially induces autoimmune disorders, such as experimental allergic encephalomyelitis, inflammatory bowel disease (IBD), and rheumatoid arthritis (RA), in which Th17 cells, as well as IL-17A-producing ␥␦ T cells, are involved (8,16,25). In this regard, since responsiveness to IL-23 should be tightly regulated, it is interesting to elucidate the mechanism for maintaining IL-23R expression on IL-17A-producing ␥␦ T cells involved in host defense against systemic C. albicans infection.…”
Section: Discussionmentioning
confidence: 99%